Blynk-Based Air Handling Unit (AHU) Air Filter Monitoring System Prototype at Juwata Tarakan Airport Terminal - Deshwita Maharani; Kurniaty Atmia; Sheilla Novita (Indonesian Journal of Multidisciplinary Scientific Studies, 2025)
The Juwata Tarakan Airport Terminal faces challenges in managing indoor air quality due to the suboptimal monitoring system of the Air Handling Unit (AHU) filter, which plays an important role in maintaining passenger comfort and health. Filter cleaning or replacement is currently done manually and reactively after a decline in air quality. This study aims to design an IoT-based air filter monitoring system for the AHU using the Blynk application. The system utilizes the Sharp GP2Y1010AU0F dust sensor and the ESP32 microcontroller, along with an LM2596 voltage regulator module to adjust the power supply. Test results show that the system can detect dust concentration in real-time and send notifications via the app and email when the threshold is reached. This system enables more efficient and predictive filter maintenance. Thus, this monitoring system can support improved energy efficiency and environmental comfort at airport terminals.